A NOVEL STABILITY-INDICATING REVERSE PHASE LIQUID CHROMATOGRAPHIC METHOD FOR THE SIMULTANEOUS ESTIMATION OF METFORMIN AND TENELIGLIPTIN IN PURE AND PHARMACEUTICAL FORMULATIONS - Swetha, A.; Kuber, B. Ramya (International Journal of Applied Pharmaceutics, 2018)
Objective: The present method was proposed to develop a simple, sensitive, rapid, accurate and stability-indicating reverse phase-high performance liquid chromatographic (RP-HPLC) method for the simultaneous estimation of metformin and teneligliptin in pure and pharmaceutical formulations. Methods: The chromatographic separation was done on Discovery [250 mm X 4.6 mm: 5 Î¼m is particle size] using a mobile phase composed of 0.1% orthophosphoric acid buffer: acetonitrile [65:35, v/v], the flow rate is 1 ml/min and the detection was carried out with a photodiode array (PDA) at 260 nm. Results: The retention time of metformin and teneligliptin were found to be 2.517 min and 3.687 min, respectively. Stability indicating studies were conducted under the guidelines of an international conference on harmonization [ICH] Q1A R2 and the developed method was validated as per the guidelines of ICH Q2 R1. The linearity was found in the range of concentration of 125-750 Î¼g/ml and 5-30 Î¼g/ml for metformin and teneligliptin. The lower limit of detection (LOD) and lower limit of quantification (LOQ) was found to be 0.02Î¼g/ml and 0.07 Î¼g/ml for metformin and 0.19 Î¼g/ml and 0.56 Î¼g/ml for teneligliptin, respectively. Conclusion: A novel stability-indicating reverse phase liquid chromatographic method developed for the simultaneous estimation of metformin and teneligliptin. The proposed method was adopted for the routine estimation of metformin and teneligliptin in bulk and pharmaceutical dosage forms.